ERANCANGAN SISTEM INFORMASI PENDAFTARAN ANGGOTA UKM KAMPUS UNIVERSITAS UBUDIYAH INDONESIA - Prasetya Wardana; M. Fazil (Ubudiyah Indonesia University, 2021)
The Student Activity Unit at the Ubudiyah Indonesia University (UUI) campus is a place for students to channel theirrespective hobbies, talents, arts and hobbies. In the case of this Student Activity Unit a registration activity that canbe carried out quickly and practically is needed so that it is able to support and process all the data that isregistered registrants, but to register there are still many obstacles encountered because the system used is stillmanual. To optimize and improve the Student Activity Unit registration service so as to make it easier for studentsto register, there is a need for reliable and well-organized data processing in support of the decision making process.Data processing system in question is a data processing system that is done computerized. So we get a goodregistration processing system. This information system application is created using the PHP programming languageand MySQL database and uses the Codeigniter framework. Users of this system are students who want to join theStudent Activity Unit on the campus of the Indonesian Ubudiyah University